Diagnostic Value of Radiomics Analysis in Contrast-Enhanced Spectral Mammography for Identifying Triple-Negative Breast Cancer - Zhang, Yongxia; Liu, Fengjie; Zhang, Han; Ma, Heng; Sun, Jian; Zhang, Ran; Song, Lei; Shi, Hao (Frontiers in Oncology, 2021)
Purpose To evaluate the value of radiomics analysis in contrast-enhanced spectral mammography (CESM) for the identification of triple-negative breast cancer (TNBC). Method CESM images of 367 pathologically confirmed breast cancer patients (training set: 218, testing set: 149) were retrospectively analysed. Cranial caudal (CC), mediolateral oblique (MLO), and combined models were built on the basis of the features extracted from subtracted images on CC, MLO, and the combination of CC and MLO, respectively, in the tumour region. The performance of the models was evaluated through receiver operating characteristic (ROC) curve analysis, the Hosmer-Lemeshow test and decision curve analysis (DCA). The areas under ROC curves (AUCs) were compared through the DeLong test. Results The combined CC and MLO model had the best AUC and sensitivity of 0.90 (95% confidence interval: 0.85-0.96) and 0.97, respectively. The Hosmer–Lemeshow test yielded a nonsignificant statistic with p-value of 0.59. The clinical usefulness of the combined CC and MLO model was confirmed if the threshold was between 0.02 and 0.81 in the DCA. Conclusions Machine learning models based on subtracted images in CESM images were valuable for distinguishing TNBC and NTNBC. The model with the combined CC and MLO features had the best performance compared with models that used CC or MLO features alone.